Structure Determination of Organic Compounds Tables of Spectral Data - Pretsch, Ernoe; Bühlmann, Philippe; Affolter, Christian (Springer Berlin Heidelberg, 2000)
This volume presents - in the form of texts, tables, charts and graphs - a modern compilation of spectroscopic reference data for IR, UV/vis, 1H- and 13C-NMR, MS (incl. prototype spectra of almost every important class of organic compounds and spectra of MALDI and FAB matrix materials) and is intended as a short textbook and a hands-on guide for interpreting experimental spectral data and elucidating the structure of the respective compound behind it. The concise texts include special chapters on fragmentation rules in mass spectrometry and on currently used multipulse and 2D NMR techniques. The book is primarily designed for students to be used during courses and exercises; advanced learners may use this book to supplement the understanding of extended textbooks on the topic. The use of the book requires only basic knowledge of spectroscopic techniques, but is structured in such a way that it will support practitioneers routinely faced with the task of interpreting such spectral information, and it will serve as a data reference for specialists in the field
Keywords: Chemistry; Analytical Chemistry; Organic Chemistry; Physical Chemistry; Industrial Chemistry/Chemical Engineering; Analytical chemistry; Organic chemistry; Physical chemistry; Chemical engineering; Organische Verbindungen; Spektrum; Tabelle; Strukturaufklärung; Struktur; Spektroskopie; Datensammlung